Editorial: Innovations in agrometeorology - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2004)
When Samuel Morse invented the telegraph in 1843, meteorologists were among the first to promote the new technology, as it allowed them to communicate weather observations over large distances in real time.